Predicting the Future: An Analysis of Employer’s Use of Predictive Artificial Intelligence in Professional Sports - Grant Atwood (Washington University Journal of Law and Policy, 2025)
As artificial intelligence (AI) becomes embedded in everyday life, professional sports teams are testing its limits. With predictive AI now helping teams identify athletes at risk of future injuries, sports leagues stand at the forefront of a legal and ethical dilemma. This Note explores the intersection of predictive AI and the Americans with Disabilities Act (ADA), arguing that while professional sports teams do not violate the ADA by acting on fears of future injury with healthy athletes, the principles of the ADA should lead to the opposite conclusion. Drawing on precedent cases and agency interpretations, this Note explains how the ADA protects against discrimination based on current or past impairments—but not potential future injuries. While legislative action could provide a solution, this Note recommends that player unions should pursue action through collective bargaining to set boundaries around predictive AI in their respective leagues.
Keywords: ADAAndAI; FutureInjuryRights; AIXSportsLaw